Pengaruh Derajat Pengapian terhadap Kinerja Motor Bakar 6 Langkah Berbahan Bakar Etanol - Razi, Misru; Siswanto, Eko; Wijayanti, Widya (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2019)
The six-stroke spark ignition engine has the potential to be developed as a new alternative to future motor fuel technology. The development of motor vehicles will be directly proportional to the use of rising fossil fuels. It is, therefore, necessary to have renewable alternative fuel, in which one of them is using ethanol fuel. Characteristics of the ethanol fuel are different from fossil fuels so the ignition timing is needed to be modified. The purpose of this study was to determine the effect of the ignition degree on the performance of a 6-stroke spark-ignition engine fuel using ethanol. This research is worked out directly by experimental and testing on the intended object. The test was carried out on an ethanol-fueled 6-step spark ignition engine with variations in the ignition angle at 240,260 and 280. Each variation was tested for a rotation interval of 600 rpm from 2400 rpm to 7200 rpm. The results show that ignition degree greatly affects performance. The ignition angle of 280 produced better torque, effective power, effective specific fuel consumption and effective thermal efficiency than those of the ignition degrees at 240 and 260 (standard angle ). This is due to the use of ethanol fuel which has a slower combustion speed. Based on this fact, it is necessary to advance the ignition angle so that the explosive power of the air-fuel mixture is increasing. Low fuel consumption and better effective thermal efficiency were observed for 280 ignition degrees compared to 240 and 260 ignition degrees.